Cerebrospinal Fluid Protein Changes in Preeclampsia. Issue 1 (July 2018) - Ciampa, Erin; Li, Yunping; Dillon, Simon; Lecarpentier, Edouard; Sorabella, Laura; Libermann, Towia A.; Karumanchi, S. Ananth; Hess, Philip E.
Abstract : The molecular mechanisms underlying seizure susceptibility in preeclampsia are unknown. We hypothesized that altered expression of distinct proteins in the cerebrospinal fluid (CSF) may reflect pathophysiological changes in the central nervous system that contribute to the neurological manifestations of severe preeclampsia. We obtained CSF samples from 13 patients with preeclampsia and 14 control patients during spinal anesthesia before delivery and analyzed them by SOMAscan, an aptamer-based proteomics platform for alterations in 1310 protein levels. Ingenuity Pathway Analysis was conducted to highlight relationships between preeclampsia-specific proteins found to be significantly altered. For 2 of the target proteins, we validated the difference in CSF concentrations by ELISA. SOMAscan revealed 82 proteins, whose expression levels were significantly different ( P <0.05) in CSF from patients with preeclampsia versus controls. Principal component analysis achieved perfect separation of the preeclampsia and control groups in 2 dimensions. The differentially expressed proteins converge around 4 signaling molecules: TGF-β (transforming growth factor-β), VEGFA (vascular endothelial growth factor A), angiotensinogen, and IL-6 (interleukin-6). Within the TGF-β pathway, upregulation of activin A (301.6±47.4 versus 151.6±20.5 pg/mL; P =0.0074) and follistatin-related gene (5129±347 versus 3016±188 pg/mL; P <0.0001) in preeclampsia was confirmed by ELISA. In summary, signaling pathways important for vascular remodeling, inflammation, and neuronal growth, signaling, and electrophysiology were well represented among the proteins found to be altered in CSF in patients with preeclampsia. Abstract : Supplemental Digital Content is available in the text.